Research in Attacks, Intrusions and Defenses 15th International Symposium, RAID 2012, Amsterdam, The Netherlands, September 12-14, 2012, Proceedings - Balzarotti, Davide; Stolfo, Salvatore J.; Cova, Marco (Security and Cryptology, 2012)
This book constitutes the proceedings of the 15th International Symposium on Research in Attacks, Intrusions and Defenses, former Recent Advances in Intrusion Detection, RAID 2012, held in Amsterdam, The Netherlands in September 2012. The 18 full and 12 poster papers presented were carefully reviewed and selected from 84 submissions. The papers address all current topics in virtualization, attacks and defenses, host and network security, fraud detection and underground economy, web security, intrusion detection.